2023
DOI: 10.3389/fcimb.2023.1139796
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of β-lactam antibiotics resistance and biofilm formation by Staphylococcus epidermidis is associated with isookanin

Abstract: IntroductionBiofilm formation is the major pathogenicity of Staphylococcus epidermidis (S. epidermidis), which enhances bacterial resistance to antibiotics. Isookanin has potential inhibitory activity on biofilm.MethodThe inhibiting mechanisms of isookanin against biofilm formation through surface hydrophobicity assay, exopolysaccharides, eDNA, gene expression analysis, microscopic visualization, and molecular docking were explored. Additionally, the combination of isookanin and β-lactam antibiotics were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The EPS production of S. epidermidis ATCC 35984 treated with blank nanogels, quercetin, and PQ-nanogels was determined as reported elsewhere [ 15 ]. The EPS of S. epidermidis ATCC 35984 (1 × 10 6 CFU/mL) treated with different concentrations (64 and 128 μg/mL) of quercetin and PQ-nanogels were extracted and precipitated using 95% ethanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EPS production of S. epidermidis ATCC 35984 treated with blank nanogels, quercetin, and PQ-nanogels was determined as reported elsewhere [ 15 ]. The EPS of S. epidermidis ATCC 35984 (1 × 10 6 CFU/mL) treated with different concentrations (64 and 128 μg/mL) of quercetin and PQ-nanogels were extracted and precipitated using 95% ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…The eDNA production of S. epidermidis ATCC 35984 treated with blank nanogels, quercetin, and PQ-nanogels was determined, as reported previously [ 15 ]. Briefly, after S. epidermidis ATCC 35984 (1 × 10 6 CFU/mL) was grown in contact with quercetin and PQ-nanogels (64 and 128 μg/mL) at 37°C for 24 h, the samples were washed with PBS, and mixed with a Tris-ethylenediaminetetraacetic acid (EDTA) buffer solution.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, molecular docking can assist in identifying the interaction mechanism of an antibiofilm agent with its target molecule. For instance, a study by Ren [14] showed that isookanin could bind to biofilm-related proteins and interrupt biofilm formation in Staphylococcus epidermis.…”
Section: Molecular Dockingmentioning
confidence: 99%